2006
DOI: 10.1109/tpwrd.2005.852340
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Method for Detection of Partial Discharges in Transformers

Abstract: A correlation method is proposed for the location of partial discharge within a winding. Theoretical simulations and experimental results on a lumped parameter model of a winding are shown to prove the feasibility of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Figure 4 shows the simulated and estimated voltage at node 5 using (12) for source applied to the input terminal. In all the cases, a constant excitation source of 1 V AC is applied and frequency is swept from 1 Hz to 300 KHz with the frequency resolution of 3 Hz collecting about 100 K sample.…”
Section: Validation Of the Analytical Expressionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the simulated and estimated voltage at node 5 using (12) for source applied to the input terminal. In all the cases, a constant excitation source of 1 V AC is applied and frequency is swept from 1 Hz to 300 KHz with the frequency resolution of 3 Hz collecting about 100 K sample.…”
Section: Validation Of the Analytical Expressionsmentioning
confidence: 99%
“…8 Apart from the mentioned theoretical literature, some experimental study with resistive circuit has been conducted in Denardo et al, 5 which found that with the addition of loops in the circuit, there is a rapid exponential convergence of the input resistance to the golden ratio. To models these windings, different equivalent networks are used, such as ladder networks, 12,13 Multi-Conductor Transmission Line (MTL), 14 and hybrid. 9 The pioneer works in the field of the infinite resistive network have been done by Zemanian.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Granger causality analysis is a statistical hypothesis test to calculate whether one time series of data is useful in forecasting another data and it finds only "predictive causality" [20] than other linear methods [21][22][23][24]. Granger causality analysis is based on multiple regression analysis.…”
Section: Principle Of Granger Causality Analysis For Impulse Fault Dementioning
confidence: 99%